Simultaneous atmospheric correction and quantification of suspended particulate matter in the Guadalquivir estuary from Landsat images - Capintero,Mariam (2020)
Earth observations (EOs) following empirical and/or analytical approaches are a feasible alternative to obtain spatial and temporal distribution of water quality variables. The limitations observed in the use of empirical approaches to estimate high concentrations of suspended particulate matter (SPM) in the estuarine water of Guadalquivir have led the authors to use a semi-analytical model, which relates the water constituents’ concentration to the water leaving reflectance. In this work, the atmospheric correction has been carried out simultaneously and the aerosol reflectance and backscattering coefficients of SPM obtained. The results are validated using in situ SPM data series provided by a monitoring network in the study area. The results show that the model allows us to successfully estimate backscattering coefficients of SPM in the estuary, differentiating clear and turbid water and using two ε( 4,5) .These considerations improve the value of R2 from 0.68 (single ε( 4,5) ) to 0.86 (two ε(4,5)) on 18 May 2009. This method could be used as a preliminary approach to obtain SPM concentration in the Guadalquivir estuary with the limitations that the model shows for turbid waters.